Synthesis of Hydrogel Based on Poly (Acrylic Acid–Co-Vinyl Acetate) Grafted on Modified Recycled Cellulose for Use in Fertilizer Slow-Release System - Soheila Nazeri; Peyman Najafi Moghadam (Advances in Polymer Technology)
The aim of this work is a synthesis of suitable hydrogel to produce slow-release fertilizer using recycled cellulose which is obtained from waste paper. For this purpose, initially, we extracted alpha cellulose from waste paper and modified it to obtain carboxymethyl cellulose (CMC). Then, the CMC was converted to a suitable hydrogel through in situ graft copolymerization of acrylic acid and vinyl acetate in the presence of methylene bisacrylamide as a crosslinker. The various factors that affect hydrogel synthesis, such as the amounts of CMC, monomers, initiator, and crosslinker, were evaluated. In the optimized formulation, the weight ratio of monomers to CMC is 7, the molar ratio of monomers to each other is 1, and the crosslinker is used as 3 molar percent of monomers. The products were characterized using Fourier transform infrared, thermal gravimetric analysis, and scanning electron microscope analyses. The swelling behavior of the synthesized hydrogels was evaluated in different environments, such as distilled water, tap water, salt water, and different pH levels. The swelling ratio increases with an increase in pH level. Between the synthesized hydrogels, the best one was selected for slow-release fertilizer production and loaded with 20-20-20 fertilizer (NPK), and the release behavior was evaluated. In an alkaline pH, there was a long time for NPK release within a slow-release medium and even after 361 h, the release process was continued. Also, the performance of the fertilizer-loaded hydrogel in soil using water holding capacity and water retention ratio tests were evaluated.